i-Thaharah - Ismail, Khairah; Abd Zamani, Siti Nor Haliza; Abdul Hamid, Norakmal; Ilias, Muhamad Zariff; Farhana, Farhana (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Fiqh Thaharah is a topic about cleanliness consisting of extensive discussions on the subtopics thaharah haqiqiyah which discusses on cleanliness from excrement and thaharah hukmiyyah which discusses on cleanliness from hadas.[1] Observing thaharah or ‘cleanliness’ is an obligatory upon every Muslim, thus considered as one of the pillars of Islam. Only with clarity and great understanding on the subject would ensures a Muslim the validity of the acts of ‘ibadah (worship). Nevertheless, confusions and obscurity within the matter of hukum or laws concerning Fiqh Thaharah are still exist among Muslims. Religious studies are usually delivered by teachers to students in classes with a traditional way of lecture and a least engaging manner whereby students lack active interaction of the topic during classes. This causes a lack of interest in a student’s viewpoint as the passive interaction bores them and results in their difficulty of understanding the topics. Therefore, ‘gamification’ method needs to be integrated into the teaching and learning processes in order to help students and serves as an alternative to enhance understanding of the topic. This method could also assist in clarifying the topic to the public. Thus, i-Thaharah is an innovation on board games that concentrate on the understanding of fiqh knowledge based on Fiqh Thaharah in accordance to as-Shafi’e sect. A new product generated as a medium of education to heighten players’ understanding in the topic of Fiqh Thaharah. The product objective is to provide public exposure about Fiqh Thaharah according to as-Shafi’e sect. Besides that, the product introduces an interactive way of teaching and learning the topic. Furthermore, it provides a way of evaluating a person’s mastery on the topic in a more casual manner through educational games or also known as edutainment and becomes another alternative of preaching Islam to the public, in particular to Muslims. Hence, this product becomes an alternative medium in learning a particular issue of thaharah as it is produced in a form of a user friendly interactive game.